Antioxidant Body Lotion Formulation From Yakon Leaf Extract (Smallanthus Sonchifolius) - Khaisya Sabila; Bangkit Riska Permata; Siwi Hastuti (International Journal of Health Engineering and Technology, 2026)
Free radicals due to UV exposure, pollution, and the environment damage the skin and accelerate premature aging, so natural antioxidants are needed. This study aims to formulate and evaluate antioxidant body lotion from ethanol extract of yacon leaves (Smallanthus sonchifolius). Semi-quantitative laboratory experimental research used old yacon leaves from Wonosobo as a purposive sample (1,897 g of dried simplicia). Instruments include a UV-Vis spectrophotometer for DPPH (515 nm) test, a Brookfield viscometer, and a pH meter. Data analysis used IC₅₀ regression and physical quality standards (SNI). The results showed that the IC₅₀ of the extract was 28.08 ppm (very strong, <50 ppm), positive phytochemical screening (phenolics, flavonoids), and all lotion formulas (F0-F3: 0-10% extract) met physical standards (pH 4.6-6.2, viscosity 2,187-9,230 cps, O/W emulsion). Formula F1 (2.5%) was optimal overall. The conclusion is that yacon leaf extract has strong potential for the development of a stable body lotion.